Critical role: the mighty nein origins, volume 1 ebook - Castellucci, Cecil (Critical Role: The Mighty Nein Origins (2022), 2023)
Critcal Role's The Mighty Nein Origins is collected for the first time!This first of two volumes collects the whimsical, tragic, and sometimes haunting backstories of Jester Lavorre, Caleb Widogast, Yasha Nydoorin, and Nott the Brave. Delve deep into their pasts and witness what led them to the Mighty Nein.This hardcover collection features stories and art by fan-favorite Critter creators, in direct consultation with the cast of Critical Role! It's a must for any fan's library.Collects:• Critical Role: Mighty Nein Origins: Jester Lavorre• Critical Role: Mighty Nein Origins: Caleb Widogast• Critical Role: Mighty Nein Origins: Yasha Nydoorin• Critical Role: Mighty Nein Origins: Nott the Brave